A Library of ROS‐Catalytic Metalloenzyme Mimics with Atomic Metal Centers (Adv. Mater. 16/2022). Issue 16 (21st April 2022) - Cao, Sujiao; Zhao, Zhenyang; Zheng, Yijuan; Wu, Zihe; Ma, Tian; Zhu, Bihui; Yang, Chengdong; Xiang, Xi; Ma, Lang; Han, Xianglong; Wang, Yi; Guo, Quanyi; et al.
Abstract : Biocatalysts In article number 2200255, Yi Wang, Li Qiu, Chong Cheng, and co‐workers report a library of reactive oxygen species (ROS)‐catalytic metalloenzyme‐mimics with different types of atomic metal centers; the catalytic activities, substrate selectivities, and ROS products are compared. These biocatalysts show high ROS‐catalytic performances and it is found that the catalytic activities are highly related to the electronic structures of the metal centers.